2013
DOI: 10.1371/journal.pone.0063045
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA Sensor IFI16 as Circulating Protein in Autoimmune Diseases Is a Signal of Damage that Impairs Endothelial Cells through High-Affinity Membrane Binding

Abstract: IFI16, a nuclear pathogenic DNA sensor induced by several pro-inflammatory cytokines, is a multifaceted protein with various functions. It is also a target for autoantibodies as specific antibodies have been demonstrated in the sera of patients affected by systemic autoimmune diseases. Following transfection of virus-derived DNA, or treatment with UVB, IFI16 delocalizes from the nucleus to the cytoplasm and is then eventually released into the extracellular milieu. In this study, using an in-house capture enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…IFI16 is a target for autoantibodies and several studies have shown the presence of anti-IFI16 autoantibodies in chronic autoimmune diseases such as SLE [64], systemic sclerosis [65], rheumatoid arthritis [66] and Sjö gren's syndrome [67]. IFI16 is known to relocalise from the nucleus to the cytosol following UV treatment or viral DNA detection.…”
Section: Disease Related Roles Of the Pyhin Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFI16 is a target for autoantibodies and several studies have shown the presence of anti-IFI16 autoantibodies in chronic autoimmune diseases such as SLE [64], systemic sclerosis [65], rheumatoid arthritis [66] and Sjö gren's syndrome [67]. IFI16 is known to relocalise from the nucleus to the cytosol following UV treatment or viral DNA detection.…”
Section: Disease Related Roles Of the Pyhin Proteinsmentioning
confidence: 99%
“…It is hypothesised that IFI16 can also be released into the extracellular milieu. This extracellular IFI16 can in turn bind to the plasma membrane of endothelial cells, and down regulate both their migratory activities and tube morphogenesis [66]. In this context IFI16 may be acting as an alarmin, propagating the stress signal and causing further damage.…”
Section: Disease Related Roles Of the Pyhin Proteinsmentioning
confidence: 99%
“…In addition to its role in defense against foreign DNA, the aberrant activity of IFI16 is also associated with several autoimmune disorders, such as systemic lupus erythematosus and Sjögren syndrome. IFI16 is involved in the onset and progression of these diseases not only by generating abnormally high levels of the proinflammatory cytokines but also by being recognized as an autoantigen by the host adaptive immune system (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Nuclear IFI16 is induced in the cytoplasm of stratified squamous epithelia in response to UVB exposure and acts as a mechanism of auto-antigen processing in SLE [19] . Meanwhile, endogenous IFI16 released by apoptotic cells acts as a novel alarmin, binding to neighbor cells and propagating the damaged-signal [32] . In addition, nuclear IFI16 is relocalized to the cytoplasm leading to proteasomal degradation by infection with HSV-1 [33] .…”
Section: Resultsmentioning
confidence: 99%